THE USE OF SOCIAL MEDIA FOR LEARNING ENGLISH - Rahmawati Dwi Handayani; Muh Syafei; Aisyah Ririn Perwikasih Utari (Prominent, 2020)
abstract. The objective of the research is to find out the kinds of social media used by fourth semester students of English Education Department of Universitas Muria Kudus for learning English. The researchers used descriptive qualitative research and the data was collected by the use of questionnaire. The participants are 50 students of English Education Department of Universitas Muria Kudus. The result showed that social media the students use for learning English are YouTube (94%),, Instagram (72%0, WhatsApp (62%), Twitter (32), Facebook (30%), Line (10%), Manwha (6%), Telegram  (2%), Google (2%),  Tik Tok (1%), Cake English App  (1%), Quora (1%) and Discord (1%)